Beyond intellectual property : toward traditional resource rights for indigenous peoples and local communities - Posey, Darrell Addison, 1947-; Dutfield, Graham (International Development Research Centre, 1996)
The concept of traditional resource rights (TRR) reflects the necessity of rethinking the limited and limiting concept of intellectual property rights (IPR). The TRR concept can accommodate a wide range of relevant international agreements as a basis for a sui-generis system of protection for indigenous peoples and their intellectual, natural, and technological resources. This book introduces the TRR concept in a manner organised around a series of questions that might emerge in a community when a visitor arrives to collect information or cultural or biogenetic materials. Each chapter begins with a summary of the main issues it addresses and ends with options and suggested actions. Issues discussed include who benefits from traditional resources, the rights of communities to approve or resist commercialisation, types of potential legal action, the applicability of traditional IPR, development of community systems for protecting TRR, the use of binding or non-binding international agreements, and TRR funding. Examples are included of creative strategies and unique solutions that indigenous communities have developed for protecting and benefiting from TRR.